Somatic mosaicism in a mother of two children with Pitt–Hopkins syndrome. (19th April 2013) - Steinbusch, CVM; van Roozendaal, KEP; Tserpelis, D; Smeets, EEJ; Kranenburg‐de Koning, TJ; de Waal, KH; Zweier, C; Rauch, A; Hennekam, RCM; Blok, MJ; Schrander‐Stumpel, CTRM
Abstract : Steinbusch CVM, van Roozendaal KEP, Tserpelis D, Smeets EEJ, Kranenburg‐de Koning TJ, de Waal KH, Zweier C, Rauch A, Hennekam RCM, Blok MJ, Schrander‐Stumpel CTRM. Somatic mosaicism in a mother of two children with Pitt–Hopkins syndrome. Pitt–Hopkins syndrome (PTHS) is a neurodevelopmental disorder characterized by intellectual disability, unusual face and breathing abnormalities and can be caused by haploinsufficiency of TCF4 . The majority of cases are sporadic. Somatic mosaicism was reported infrequently. We report on a proband with typical manifestations of PTHS and his younger brother with a less striking phenotype. In both, a heterozygous frameshift mutation (c.1901_1909delinsA, p.Ala634AspfsX67) was found in exon 19 of TCF4 . The same mutation was found at low levels in DNA extracted from the mother's blood, urine and saliva. This report of familial recurrence with somatic mosaicism in a healthy mother has important consequences for genetic counseling. We suggest careful studies in parents of other patients with PTHS to determine the frequency of germline and somatic mosaicism for TCF4 mutations.